Quasi-Hadamard Product and Partial Sums for Sakaguchi-Type Function Classes Involving q-Difference Operator - ÇETİNKAYA, ASENA; Cotirla, Luminita-Ioana (MDPI, 2022)
We create two Sakaguchi-type function classes that are starlike and convex with respect to their symmetric points, including a q-difference operator, which may have symmetric or assymetric properties, in the open unit disc. We first obtain sufficient coefficient bounds for these functions. In view of these bounds, we obtain quasi-Hadamard products and several partial sums for these function classes. Moreover, the special values of the parameters provided the corresponding consequences of the partial sums.
Keywords: Sakaguchi-type; Functionsq-difference; Operatorquasi-hadamard; Productpartial; Sums